Optimalisasi Pemanfaatan Dana Program Indonesia Pintar: Efektivitas dan Tantangan - Sapto Widodo; Zikrul Alwi; Harsono; Suyatmini (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The Indonesia Smart Program (Program Indonesia Pintar/PIP) is a government initiative that provides financial aid to help students from underprivileged families gain access to education. The objective of this research is to evaluate the efficacy of PIP implementation and pinpoint the different obstacles that arise during its field execution. By looking at a variety of sources pertaining to PIP implementation, education policy, and program assessment data, a systematic literature study is the approach taken. The results show that PIP has increased student participation and decreased dropout rates significantly. Accurate targeting, grant transfer delays, and a lack of regional outreach are some of the issues it still faces. This study recommends strengthening inter-agency coordination and improving the recipient data verification system to ensure that the utilization of PIP funds is more optimal and equitable